Analisis Determinan Kejadian Anemia Ibu Hamil Trimester III pada Era New Normal - Nurpajri, Nurpajri; Nilawati, Andi; Massi, Nasrum; Hadju, Veni; Ahmad, Mardiana; Ariyandi, Andi (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the determinants of the occurrence of anemia in pregnant women. The study used an observational analytic design with a case control with analysis using bivariate and multivariate methods. The results show that a significant relationship with the incidence of anemia in third trimester pregnant women, namely pregnancy distance, KEK status, compliance with Fe Consumption, Achievement of ANC visits and History of exposure to Covid19. The factors that most influenced the incidence of anemia were Compliance with Fe Tablet Consumption, mother's KEK status and history of exposure to Covid19. Age and history of premarital counseling were not significant to the incidence of anemia. Conclusion compliance with consumption of Fe tablets is the most influential factor on the incidence of anemia in third trimester pregnant women at new normal era. Keywords: Anemia, New Normal Era, Pregnant Women TM III